Pneumoperitoneum with Muyo Hook on Laparoscopic Cholecystectomy - Fadli Robby Amsriza; Rizka Fakhriani; Sagiran Sagiran (Faculty of Medicine Universitas Indonesia, 2023)
Gallstone migration into the cystic duct aperture can prevent bile from exiting the gallbladder during contraction. Gallbladder wall strain increases due to a distinct form of pain (biliary colic). A more prolonged cystic duct obstruction can cause acute gallbladder inflammation (acute cholecystitis). Cholecystectomy is a popular treatment for gallstone-related illnesses. We present a 49-year-old male with heartburn, nausea, and vomiting for one month, worsening in the last week. On general examination, vital signs and urine output are expected. On clinical examination, he had tenderness on the upper right quadrant abdomen, and Murphy's sign was positive. An abdominal ultrasound (US) showed multiple cholelithiasis. The patient was performed elective laparoscopic cholecystectomy with pneumoperitoneum by Muyo hook. The patient was discharged on the third day after surgery. Recent research has highlighted this unusual method. In this unique and challenging situation, Muyo Hook may be an option.